REAL OPTIONS FOR MERGERS AND ACQUISITIONS OF COMPANIES: BIMBO AND WESTON FOODS - Rodríguez Hernández, Velda Liliana (2014)
This work proposes the use of the methodology to process real financial valuation of strategic investments in mergers and acquisitions by global companies of Mexican options. Through a concrete example it shows the appropriateness of their use in the analysis of the feasibility of buying the American company - Canadian Weston Foods by the Mexican multinational company Bimbo, purchase modeling in the context of the theory of real options as an option buying applying the binomial expansion method. Determine the value of the option to purchase Weston Foods applying real options methodology by comparing it with the premium originally agreed by Bimbo. And finally, it is determined whether the purchase of Weston Foods will add value to Bimbo.